Customer-centric marketing : supporting sustainability in the digital age - Richardson, Neil; James, Jon;Kelley, Neil (London, United Kingdom : Kogan Page Limited, 2015)
Customer-Centric Marketing looks at how to become a socially responsible company whose customers want to advocate for them. Since customers are more technically-savvy than ever before, this book focuses on creating and implementing a purpose-driven digital marketing plan that sets out: what a company's values and goals are; what a company is good at; what the customers want; how communications can be used to improve internal and external relationships; what role digital communications will play. Offering an actionable plan for adopting sustainable marketing, this book explains how to meet customer expectations, improve an organization's competitive advantage, and grow a business using sustainable and responsible practices
Part 1. Changing landscapes -- Part 2. Knowing your company -- Part 3. Building relationships -- Part 4. Marketing planning -- Part 5. The marketing mix
Includes bibliographical references.
Keywords: RELATIONSHIP MARKETING